Analysis on the pattern of using the service of removable partial denture making in a dental laboratory in surabaya - Setyowati, Okti; Kusdarjanti, Endang (Folia Medica Indonesiana, 2017)
The making of removable denture is performed by a dental laboratory. To facilitate the identification, according to Kennedy classification, classes are divided onto groups, the Kennedy class I, II, III and IV. To suit with the needs of the dental laboratory tasks commonly done, priority are necessary for common cases and should to be taught to students of Dental Health Technology Diploma. In Surabaya, research of various cases of removable partial denture with the various Kennedy classifications has never been done before. This study was to analyze the pattern of service for the removable partial denture manufacture in dental laboratory at Surabaya (2011 – 2013). The research is an observatory analytic. The population is all dental laboratories located around the campus of the Faculty of Dentistry Airlangga University Surabaya. The sample was the whole population is willing to become respondents. Sampling by total sampling. The method of collecting data using secondary data from a dental laboratory in Surabaya from 2011 until 2013. The note is cases removable denture according to the classification of Kennedy that Kennedy Class I, II, III and IV. Also of note kinds of materials used to make the denture base that is heat cured acrylic resins, thermoplastic resins and metals coherent. The data is a compilation table charting the frequency until needed, then analyzed using cross tabulation. Mostly denture type is flexible type and the least is metal framework. Most cases by classification Kennedy is followed by class II class III and class II and more recently is the fourth. In conclusion, in 2011 and 2013 the manufacture of removable partial dentures according to the classification of Kennedy Class III is the most common in both the upper arch and lower jaw, followed by Class II, Class I and Class IV. In 2012 which is the highest grade III followed by class II, class IV and class I. The denture type most used is a flexible denture, followed acrylic denture and the last is the metal framework.